Bstan pa skyoṅ paʼi dam can chen po rnams kyi phrin las dṅos grub kyi rol mtsho źes bya ba bźugs - Gter-bdag-gliṅ-pa ʼGyur-med-rdo-rje, 1646-1714 (s.n., 1970)
Rituals for the propitiation of protective deities of the Lho-gter rites of the Nyingmapa sect of Tibetan Buddhism.